Understanding ordinary landscapes - Groth, Paul Erling; Bressi, Todd W. (Yale University Press, 1997)
"Whereas traditional studies in this field have been of rural life, most of the authors in this collection take on urban subjects, and with them the challenging issues of power, class, race, ethnicity, subculture, and cultural opposition. J.B. Jackson, the field's foremost proponent and practitioner, writes on the nature of the vernacular house and the garage. Other contributors include James Borchert on the social stratification of Cleveland suburbs, Rina Swentzell on Native American and U.S. government environments among the Santa Clara Pueblo in New Mexico, Reuben Rainey on the Gettysburg battlefield, Dolores Hayden on the potentials of urban landscape documentation, and Denis Cosgrove on spectacle and society. Still other authors - Wilbur Zelinsky, Richard Walker, Dell Upton, David Lowenthal, Jay Appleton, and Robert Riley - explore vision and space as sources of social interpretation. The book also includes a historical review of recent trends in the field of landscape studies and an annotated bibliography."--Jacket